The Influence Of Online Marketing And Content Creators On Income Increase In MSMEs In Purwakarta - Azidan, Ikhsan Azidan; Permana, Adi Fandi Permana; Aulia, Riska Aulia; Agustina, Sinta Agustina; Agustina, Windi Agustina (ICON Publisher, 2025)
This study aims to identify and analyze the influence of online marketing and the role of content creators on increasing income in Micro, Small, and Medium Enterprises (MSMEs) in Purwakarta. In the increasingly developing digital era, MSMEs are faced with new challenges and opportunities that require effective marketing strategies to survive and thrive. Data were taken from an online questionnaire to respondents, namely MSME actors in Purwakarta Regency. Partial least squares structural equation modeling and mediation analysis used the bootstrap method. This study reveals several important results regarding the influence of online marketing and the role of content creators on increasing income in MSMEs in Purwakarta. First, online marketing has been shown to significantly increase the visibility and sales of MSME products. Social media platforms, websites, and marketplaces are effective tools in reaching wider consumers and diversifying sales channels. Second, content creators play a crucial role in strengthening brand awareness and building closer relationships with consumers. Collaboration with content creators helps MSMEs to create interesting and relevant content, so that it can increase consumer engagement and expand market reach. This study will evaluate the extent to which online marketing can increase the visibility and sales of MSME products and how content creators contribute to expanding market reach and strengthening brand awareness.